Temporary Teacher Application System for PPD Dungun (e-KGSK) / Norhidayah Kamarudin - Kamarudin, Norhidayah (2012)
Current manual system for application of Kumpulan Guru Simpanan Kebangsaan (KGSK) is believed to be cost and time consuming, and requires a lot of documentation. Its give problems to the applicant, school parties as well as PPD Dungun staff itself. Temporary Teacher Application System for PPD Dungun (e-KGSK) is derived in order to overcome the problem encountered within the manual system. The methodology used in the development of the system was adapted from System Development Life Cycle (SDLC) Waterfall Model. The Waterfall Model is a sequential development process through the phases of preliminary study, analysis, design, implementation, testing and documentation. E-KGSK allowed applicants to access their profile and update or delete the information. This system also enable the schools’ administrator to request for temporary teacher from PPD Dungun and it store the data in the permanent database. At last, PPD Dungun’s staff, applicants (public community), and school’s administrator will test the developed system for system usability and user acceptance testing. Based on the evaluation done, it is found that e-KGSK is rated highly in its user interface design and system usability. In conclusion, this system is hoped to give benefits to school’s administrators, applicants and PPD Dungun staff in order to manage the applicant’s data and reduce time needed for application of KGSK’s members.